Food Basket Intervention for Ante-Natal attendance in Nafada LGA, Gombe State - Olumuyiwa, Babaranti; Eban, Emmanuel; Musa, Bilkisu Dauda; Kholi, Gladys Yakubu; Hassan, Ibrahim Aliyu; Onyekachi, Mabel; Loko, Ekundayo; Kuma, Lanem Law; Adeniyi, Kehinde; Solanke, Ojuolape; Oluwafunmilola Olotu, Joan (Kashere Journal of Politics and International Relations, 2025)
The study looks at the immediate outcome on food basket intervention for increase in antenatal care attendance in Nafada Local Government Area, Gombe State, Nigeria, implemented by the National Social Safety Nets Programme under the Accelerating Nutrition Result in Nigeria. The food basket intervention aims to alleviate micronutrient deficiencies, particularly anemia and vitamin A deficiency, among pregnant women, which are critical contributors to maternal and infant mortality. Despite the high rates of maternal and infant mortality in Nafada, with only 27% of women delivering in health facilities, the intervention seeks to enhance maternal health outcomes and encourage regular ANC attendance. Utilizing a desk review of secondary data from the Gombe State Health Sector Strategic Plan and administrative records from primary health care facilities, the study analyzes trends in ANC attendance from 2021 to 2024. Results indicate a significant increase in ANC attendance, from 10,522 in 2021 to 20,183 in 2024, demonstrating a cumulative increase of 91%. Qualitative data further supports these findings, revealing reduced hunger among beneficiaries and increased health facility attendance. The study concludes that the food basket intervention has positively influenced ANC attendance, thereby driving demand for health services and prompting government responses to improve supply. Recommendations include expanding the food basket intervention to other LGAs and enhancing behavioral change communication to promote ANC attendance among pregnant women. Further research is suggested to explore the sustainability of the intervention and its long-term effects on maternal health outcomes.